A note on the effects of remittances and overseas migration on some Philippine statistics - Daway, Sarah Lynne S.; Ducanes, Geoffrey M. (The Philippine Review of Economics, 2015)
The Philippines is peculiar in that a significant portion of its population is dispersed globally, sending remittances that have exceeded 8 percent of its gross domestic product (gdp) in recent years. For the last two decades, the country has enjoyed a steady flow of remittances from overseas Filipino workers, which has not only provided an additional source of disposable income to domestic households but has also served as a buffer against economic downturns. This note shows that standard gdp accounting and current labor statistics may inadequately account for remittances and overseas migration, especially their corresponding welfare consequences. A better valuation of welfare and living standards requires alternative measures that would better capture the migration phenomenon.